Modelagem e simulação do tratamento de água oleosa usando hidrociclones - Freitas, Andréa Gonçalves Bueno de (2012)
The increase of the industrial pollution has been carrying the organs of environmental control to review the legislation in force and to limit in a more rigorous form the discards of industrial effluent. As opposed, the companies have been improving the treatment systems of their effluent, applying new technologies. In the petroleum industry, in the oil-water separation, are used floatation chamber and hydrocyclones. The floatation seeks to recover the oil residue through gravitational separation, while the hydrocyclones try to accelerate this process with the use of the centrifugal force. The hydrocyclones in study are equipment constituted of a cylindrical part and two conic parts joint, in which the supply is constituted by two entrances involute, diametrically opposite, presenting a normal axis to the equipment and positioned tangentially to the lateral wall of the cylinder. The separator has two openings for exit, axis positioned to the equipment, one of them, called overflow, placed near to the supply section and to another, called underflow, placed near to the vertex of the conic body of the hydrocyclone. The analysis of the fluid-dynamic behavior of the hydrocyclone was led through the numeric simulation of the treatment of water produced, applying methods of Computational Fluid-dynamic (CFD). In the used computational tool, CFX, it is possible to build the geometry, draw the numeric mesh, adjust the simulation parameters, solve and to analyze the results, being able to be applied for several kinds of flow. It accomplished an experimental planning with the goal of analyzing the influence of the geometry in the separation efficiency of the hydrocyclone, in other words, know which variables were more important for the separation efficiency. To evaluate the performance of the equipment were calculated the Flow Ratio (Rf) and the Reduced Grade Efficiency (G ), for each geometry. Due to the great number of tested variables, whatever Dc, Do, Du, Hc, VF e L1 it opted to not analyze the effect of each one in separated, but the interactions of these. The different numeric simulations were considered as computational experiments. In all the 19 computational experiments, the simulations were initiated with the turbulence model k-e, these last used as initial values for the simulations with the turbulence model SSG, because this last is what best represents the flow in the hydrocyclone. The analyses done in the Essential Regression show that the variables which the most influence the separation efficiency are the overflow and underflow diameters. The reduced grade efficiencies stayed well distributed in the range 0-96%, what shows that the choice of the size of tried drop (250 mm) was adequate. The greatest reason values of fluid were obtained for Do/Du @ 1.0 and the minors, excluding Rf = 0, for Do/Du @ 0.2. In the studied intervals, the greatest Reduced Grade Efficiency values are obtained with the biggest values of Do and the smallest of Du. The smallest results of Flow Ratio are obtained with the smallest values of Do and the biggest values of Du.